Distribution of permanent canine agenesis in Down syndrome: 15 cases from a Centre for Special Care Dentistry. (31st July 2014) - Reuland‐Bosma, Wimke; Reuland, Merijn C.; Bronkhorst, Ewald
ABSTRACT The purpose of this study was to investigate the distribution of permanent canine agenesis in subjects with Down syndrome (DS). Subjects with canine agenesis were determined by means of panoramic radiographs from 150 DS subjects attending a center for special care dentistry. Our results confirm the high prevalence of agenetic canines in DS (21 canines, 14%). We found specific effects on the distribution both of phenotype and of location (jaw). In subjects with a mild expression of hypodontia (phenotype nonoligodontia) agenetic canines primarily occurred in the mandibula, whereas in subjects with severe hypodontia (phenotype oligodontia) agenetic canines virtually only occurred in the maxilla. In both phenotypes cooccurrence of an agenetic lateral incisor with an agenetic canine was observed in the maxilla. It was striking that canine agenesis in the mandibula did not cooccur with agenesis of other teeth. These results can be important for treatment planning.